A new addition to the Nymphalidae of Uttar Pradesh, India (Insecta: Lepidoptera) - Taslima Sheikh; Rupa De; Ratindra Pandey (SHILAP)
The present study adds a new record of Nymphalidae i.e., Phaedyma columella ophiana (Moore, 1872) for the state of Uttar Pradesh, India.